MOOD STRUCTURE ANALYSIS OF TEACHER TALK IN EFL CLASSROOM: A DISCOURSE STUDY BASED ON SYSTEMIC FUNCTIONAL LINGUISTIC THEORY - ., ZAENUL FIKRI; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Drs. I Wayan Suarnajaya,MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris, 2014)
Penelitian ini bertujuan menganalisis pembicaraan guru laki dan perempuan pada Mata Pelajaran Bahasa Inggris. Analisis tersebut dimaksudkan untuk menemukan realisasi dari Mood pada pembicaraan guru, realisasi Mood pada peran guru, dan perbedaan antara pembicaraan guru laki dan perempuan yang kaitannya dengan realisasi Mood. Penelitian ini merupakan penelitian kualitatif-deskreptif dan analisis diskursus. Data dikumpulkan melalui observasi seperti rekaman dan catatan lapangan. Data dianalisis dengan menggunakan Analisis Mood yang dipopulerkan oleh M.A.K Halliday. Untuk mendapatkan analisis yang lebih dalam, data ditrianggulasi dengan menginterview partisipan, dua guru senior dan satu pakar. Berdasarkan hasil analisis data, temuan penelitian ini dapat dinyatakan sebagai berikut: (1) Guru laki menggunakan tujuh jenis speech function dan guru perempuan menggunakan delapan jenis speech function selama proses interaksi di kelas. Semua speech function tersebut pada umumnya direalisasikan dalam dua jenis: Typical clause Mood dan Non-typical clause Mood. (2) penggunaan secara dominan hampir di semua speech function pada peran tertentu, misalnya sebagai pengontrol, menununjukkan bahwa ada hubungan antara peran guru dengan realisasi Mood. (3) ada perbedaan ujaran guru laki dengan guru perempuan di dalam memilih sistem Mood di dalam mengungkapkan makna interpersonal kepada siswa seperti: memberikan informasi, memberikan pertanyaan, meminta siswa melakukan sesuatu, dan menawarkan siswa sesuatu. Factor idiologi, kultur dan social dari para guru tersebut diyakini sebagai faktor yang mempengaruhi perbedaan tersebut. Kata Kunci : Mood Structure, Teacher Talk, EFL Classroom This study aims at analyzing male and female teacher talk in EFL classroom. The analysis was meant to find out the realization of Mood in teacher talk, the realization of Mood in teacherâs role, and the difference between male and female teacher talk in terms of speech functions in relation to Mood realization. It was designed as a descriptive-qualitative research, and discourse analysis. Data were collected through observations i.e. recording and note-taking as the main source. The data were analyzed using Mood structure analysis suggested by M.A.K Halliday. To gain deeper analysis, the data were triangulated by interviewing the participants, two senior English teachers i.e. male and female teachers, and one linguist. Based on the results of the data analysis, the findings of this research can be stated as follows: (1) Male teacher employed seven speech functions and female teacher employed eight speech functions during their classroom interaction. Those speech functions were commonly realized in two types: Typical clause Mood and Non-typical clause Mood in making interpersonal meaning among the students. (2) The dominant use of almost all speech functions in a certain role i.e. a controller role indicates that there is a relation between teacherâs role and Mood realization. (3) There are some differences of male and female teacher talk in selecting Mood system in expressing interpersonal meaning to the students i.e. in giving information, in asking a question, in demanding the students to do something, and in offering something to the students. Ideological, cultural and social factor of the teachers are believed as the contribution to the differences. keyword : Mood Structure, Teacher Talk, EFL Classroom